A figura do empregado “hipersuficiente” : uma análise da extensão da flexibilidade introduzida pela Lei N.º 13.467/2017 à luz da ordem jurídicoconstitucional brasileira - Miranda, Diogo Antonio Pereira (2023)
Law 13467/2017, known as labor reform, brought profound changes to the Brazilian Consolidation of Labor Laws (CLT), not only in the individual aspect but also in the collective and procedural aspects, which greatly affected several labor rights. Among these changes is the insertion of a new category of employees within the legal-labor system: the so-called "hypersufficient" employee, who has a greater power to negotiate employment contracts and is characterized by having a college degree and receiving a monthly salary equal to or higher than twice the Brazilian Social Security benefits ceiling (R$15,014.98, in updated values as of January 2023). Within this subject, the purpose of this research was to analyze to what extent the flexibility brought to these workers by the labor reform of 2017 can be applied without unduly affecting a fundamental right. This purpose was achieved by investigating a major problem: whether the Labor Law, which has a strongly protective bias, opens space for restricting employee rights. Based on the affirmative answer to this question, this research investigated two developments: the first is whether the possibility of the "hypersufficient" employee individually negotiating certain clauses of their contract, which prevails over the law, is supported by a constitutional and principle analysis of Labor Law. Even if the answer is affirmative, its application requires caution and has obstacles that need to be analyzed, assessed, and circumvented, which could be done, it is proposed, in a satisfactory manner by bringing the concept of vulnerability to Labor Law in addition to the concept of hyposufficiency, a general characteristic of employees. Therein lies the second development of the problem investigated by this research, which addressed the theme in three chapters, divided into three subchapters each. Using the hypothetical-deductive method, this research sought to verify whether the Labor Law, as a strongly protective discipline, leaves room for possible restrictions on workers' rights. Also, in that context, it analyzed the flexibility brought in the labor reform of 2017 to certain employees in light of the Brazilian Federal Constitution of 1988 and principles applicable to Labor Law. This research used the historical procedure, analyzing the emergence of labor law to the present day, and typological, observing the working class and its differences, especially regarding employees who can be considered "hypersufficient" by the labor reform of 2017. The interpretative method used in this research was exegetical because it was necessary to interpret and seek the reach of the labor legislation (especially the Brazilian Federal Constitution and the CLT) to answer the proposed questions. Developed qualitatively and theoretically, this research is bibliographical as to its object, relying predominantly on the existing bibliography. Labor relations need to be modernized and adapted to a time increasingly characterized by rapid social interactions without forgetting the protective principles that must govern Labor Law